Automated Vitality Evaluation of Shrimp Postlarvae via Machine Vision: A Multi-Object Tracking and Behavioral Analytics Approach - Hao Gu; Luxi Yu; Hongda Li; Ming Chen (Marine Biotechnology, 2026)

Scutellarin reduces apoptosis in R28 cells induced by continuous hydrostatic pressure combined with oxygen-glucose deprivation through the Keap1/Nrf2/NF-κB pathway - Hongda Cui; Yu Huang; Xin Xia; Jiangwei Li; Jun Peng; Yijing Yang; Qinghua Peng (Tissue and Cell, 2026)

Dynamic response of a floating offshore wind turbine under multi-stage typhoon conditions: A case study of super typhoon In-Fa - Jundong Wang; Lei Xue; Liye Zhao; Feifei Cao; Hongda Shi; Yu Xue (Ocean Engineering, 2026)

Synergistic Co-Mn bimetallic sites activate peroxymonosulfate on citrus peel biochar to achieve efficient degradation of sulfadiazine - Yunzhe Zhao; Hongda Zhang; Jian Zhang; Jiale Zhang; Jiaoyang Ji; Yong Yu; Haiyan Li (Journal of Environmental Chemical Engineering, 2026)

Pore characterization of coal cuttings based on low-field nuclear magnetic resonance: A new method - Hongda Wen; Cheng Zhai; Jizhao Xu; Yong Sun; Fei Wu; Hexiang Xu; Yu Wang (Fuel, 2026)

Integration of QuEChERS pretreatment and advanced liquid chromatography/mass spectrometry analysis for the broad-spectrum screening and simultaneous quantification of 15 mycotoxins in Citrus reticulata peel - Yu Wang; Lianxing Wang; Xue Li; Xiaoyan Xu; Feiyang Yu; Qing Tian; Yadan Zou; Qinhua Chen; Hongda Wang; Dean Guo; Wenzhi Yang (Food Chemistry, 2026)

Preparation and characterization of Ag@MOF-Amomum tsaoko essential oil/waterborne polyurethane composite films for strawberry preservation - Yuyue Qin; Hongda Yu; Haiyan Chen; Yongliang Zhuang; Qiuming Liu; Rui Cui; Cong Zhang; Charles Brennan; Yuanxiang Huang (Food Control, 2025)

Mechanical Response and Damage Mechanism of Coals Under the Hydration Reaction in the Atmosphere of CO2 - Jizhao Xu; Hongchang Liu; Sheng Qian; Hexiang Xu; Hongda Wen; Ting Liu; Zihao Wei; Zijian Yu; Zhibo Xing; Cheng Zhai (Natural Resources Research, 2025)

Numerical study of Bragg resonance reflection for wave energy converter arrays in a two-dimensional viscous wave tank - Hongjian Wu; Hongda Shi; Feifei Cao; Mingqi Yu; Meng Han; Xi Yi; Jiajun Chen (Ocean Engineering, 2025)

Highly efficient sulfadiazine removal in secondary effluent by hydrogel beads-zero-valent cobalt/diatomite: Roles of organic radicals and vacancy nanoarchitectonics - Hongda Zhang; Yunzhe Zhao; Haiyan Li; Jian Wang; Yong Yu (Journal of Environmental Chemical Engineering, 2025)

Co/kaolin-pectin/Co catalyst for activating peroxymonosulfate to degrade atrazine in water - Yongxin Guo; Hongda Zhang; Bolun Zhang; Gang Wang; Yong Yu (Journal of Environmental Chemical Engineering, 2025)

Preparation of powdery reduced iron from high-phosphorus iron ore: Effects of raw material particle size combination - Hongda Xu; Xiaojin Wen; Jue Kou; Jun Zhang; Kexin Yu; Tichang Sun (Minerals Engineering, 2025)

Synergistic catalysis of Co single atoms and nanoparticles boosts the generation of singlet oxygen: Theoretical calculation and recyclable product application - Hongda Zhang; Yunzhe Zhao; Haiyan Li; Jian Wang; Yong Yu (Chemical Engineering Journal, 2025)

Control optimization and dynamic response analysis of a combined semi-submersible floating wind turbine and point-absorber wave energy converters - Lei Xue; Nataliia Y. Sergiienko; Boyin Ding; Benjamin Cazzolato; Zhiwen Wei; Yang Yang; Feifei Cao; Hongda Shi; Yu Xue (Ocean Engineering, 2025)

Mechanically strength with water repellency: Recently advances in superhydrophobic concrete - Ziyi Dai; Hongda Guo; Yu Wang; Mingrui Wang; Yiming Zhang; Kai Qian (Journal of Cleaner Production, 2025)

Photocatalytic activation of peroxymonosulfate by oxygen doped graphitic C3N4 with oxygen vacancy for drug degradation: Theoretical calculation and recyclable products - Hongda Zhang; Yunzhe Zhao; Haiyan Li; Jian Wang; Yong Yu (Journal of Environmental Chemical Engineering, 2025)

Nitrogen-doped carbon quantum dots (NCQDs) detected to mercury ions in food monitoring - Di Shan; Huichuan Yu; Zhichao Yang; Hongda Li; Rulin Jia; Yue Zhang (Food Chemistry, 2025)

Effects of chitosan/eugenol-loaded IRMOF-3 nanoparticles composite films on reactive oxygen species metabolism and microbial community dynamics in postharvest strawberries - Yuyue Qin; Hongda Yu; Kejun Chen; Rui Cui; Jianxin Cao; Zhengxuan Wang; Zhi-Hong Zhang; Thanapop Soteyome (Food Bioscience, 2025)

Fertilizer reduction and biochar amendment promote soil mineral-associated organic carbon, bacterial activity, and enzyme activity in a jasmine garden in southeast China - Fajun Yang; Weiqi Wang; Ziwei Wu; Jiahao Peng; Hongda Xu; Maoquan Ge; Shaoying Lin; Yu Zeng; Jordi Sardans; Chun Wang; Josep Peñuelas (Science of The Total Environment, 2024)

The synergistic effect of Co atomic clusters and single atoms facilitates the Fenton-like reaction on A- and R-TiO2 - Hongda Zhang; Yunzhe Zhao; Haiyan Li; Jian Wang; Yong Yu (Journal of Cleaner Production, 2024)

Activation of peroxymonosulfate by boron nitride loaded with Co mixed oxides and boron vacancy for ultrafast removal of drugs in surface water - Hongda Zhang; Yunzhe Zhao; Chenxu Wang; Baolin Liu; Yong Yu (Journal of Environmental Chemical Engineering, 2024)

Voluntary walking related joint movement training with targeted epidural electrical stimulation enabled neural recovery for individuals with spinal cord injury - Xi Zhang; Yang Lu; Boyang Zhang; Hongda Li; Qingyu Yao; Junhong Lim; Yunyue Wei; Kaibo He; Chenhui Zuo; Yanan Sui; Bozhi Ma; Mingshan Ran; et al. (Science Bulletin, 2024)

Research on hydrodynamic characteristics of compartmented buoy wave energy converter - Tongshun Yu; Xin Gao; Hongda Shi; Zhenyu Zhang (Ocean Engineering, 2024)

Utilization of low metamorphic degree bituminous coal in direct reduction of high-phosphorus oolitic hematite and its mechanism - Kexin Yu; Wenjie Zou; Jue Kou; Chunbao Sun; Hongda Xu; Hao Dong; Bo Rao; Tichang Sun (Fuel, 2024)

Cobalt single atom anchored at C2N3 for activating peracetic acid to ultrafast degrade drugs at 4 °C - Hongda Zhang; Guanghui Xu; Chenxu Wang; Baolin Liu; Yong Yu (Journal of Environmental Chemical Engineering, 2024)

Activation of periodate by C2N3 loaded with metal single-atoms for ultrafast removal of micropollutants: Electron transfer outperforms reactive oxygen species - Hongda Zhang; Yunzhe Zhao; Haiyan Li; Jian Wang; Yong Yu (Chemical Engineering Journal, 2024)

A new butylphthalide from Ligusticum striatum DC. - Xue Xie; Hongda Zhang; Lina Liu; Fuyong Ni; Xiao Yu; Yan Zhong; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Nan Xu; Wei Xiao (Natural Product Research, 2024)

Three undescribed coumarins from the roots of Angelica pubescens - Fuyong Ni; Xue Xie; Xue Huai; Xiao Yu; Hongda Zhang; Ming Li; Jianhui Wen; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2024)

Hydrodynamic performance and energy redistribution characteristics of wind–wave hybrid system based on different WEC microarrays - Mingqi Yu; Feifei Cao; Zhiwen Wei; Meng Han; Hongda Shi; Pengfei Chen; Huiyuan Tian (Ocean Engineering, 2024)

Photocatalytic activation of sodium percarbonate by C3N5/C2N3 homojunction for rapid water purification: Efficient electron transfer of built-in electric field - Hongda Zhang; Yunzhe Zhao; Guanghui Xu; Haiyan Li; Yong Yu (Chemical Engineering Journal, 2024)

Machine learning prediction for constructing a universal multidimensional information library of Panax saponins (ginsenosides) - Hongda Wang; Lin Zhang; Xiaohang Li; Mengxiao Sun; Meiting Jiang; Xiaojian Shi; Xiaoyan Xu; Mengxiang Ding; Boxue Chen; Heshui Yu; Zheng Li; Dean Guo; et al. (Food Chemistry, 2024)

Photocatalytic activation of peracetic acid by metal–free C2N3 for efficient water purification under visible light: High–efficiency bifurcated electron transport - Hongda Zhang; Guanghui Xu; Yong Yu (Chemical Engineering Journal, 2024)

A novel competitive fluorescence colorimetric dual-mode immunosensor for detecting ochratoxin A based on the synergistically enhanced peroxidase-like activity of AuAg NCs-SPCN nanocomposite - Chenxi Ke; Yu Wu; Zichen Song; Meie Zheng; Hongda Zhu; Huiling Guo; Hongmei Sun; Mingxing Liu (Food Chemistry, 2024)

Gegenbauer-Ritz method for free vibration analysis of rotating functionally graded graphene reinforced porous composite stepped cylindrical shells with arbitrary boundary conditions - Hongda Xu; Yu Wang; Ziqiang Xu; Xiaoguang Yu (Engineering Structures, 2024)

Diabetes: a potential mediator of associations between polycyclic aromatic hydrocarbon exposure and stroke - Aikai Zhang; Hongda Zhang; Lijie Mi; Lei Ding; Zihan Jiang; Fengyuan Yu; Min Tang (Environmental Science and Pollution Research, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Calcium sulfide based nanoreservoirs elicit dual pyroptosis pathways for enhanced anti-tumor immunity - Qi Yu; Qiangwang Li; Le Tu; Yujing Zhou; Hongda Zhu; Qin Zhang; Mingxing Liu; Yao Sun (Chemical Engineering Journal, 2023)

Co single-atom C2N3 activates peroxymonosulfate for efficient degradation of sulfamethoxazole at 4 °C: A combined experimental and density functional theory study - Hongda Zhang; Guanghui Xu; Yong Yu (Chemical Engineering Journal, 2023)

Lateral load response of L-shaped steel–concrete composite shear walls using multi-partition steel tube - Yunhe Wang; Lanhui Guo; Hongda Li; Soheil Shafaei; Yue Yu (Engineering Structures, 2023)

Co single atoms anchored on straw biochar as an efficient peroxydisulfate activator for ultrafast removal of antibiotics - Hongda Zhang; Guanghui Xu; Yong Yu (Environmental Pollution, 2023)

Preparation and model construction of novel 2D nanocomposite of Zn-P-GCNN and its mechanisms of synergistic adsorption for Cu(II) and methylene blue - Meie Zheng; Fei Ma; Mingxing Liu; Mengjiao Li; Qingjie Yu; Hongda Zhu; Huiling Guo; Hongmei Sun (Journal of Cleaner Production, 2023)

Experimental investigation on the wave-oscillating buoy interaction and wave run-up on the buoy - Tongshun Yu; Tingyu Li; Hongda Shi; Zhenyu Zhang; Xingyu Chen (Ocean Engineering, 2023)

Progress of Combined Wind and Wave Energy Harvesting Devices and Related Coupling Simulation Techniques - Feifei Cao; Mingqi Yu; Bing Liu; Zhiwen Wei; Lei Xue; Meng Han; Hongda Shi (Journal of Marine Science and Engineering, 2023)
The use of combined wind and wave energy harvesting devices (CWWHDs) is an effective way to synergistically capture offshore wind and wave energy. However, the form of combined energy harvesting and coupled simulation techniques limit the development of CWWHDs. This paper classifies the existing CWWHDs based on wave energy converters and offshore wind turbines, summarizes the theoretical background and implementation forms of the numerical simulation of CWWHDs, and focuses on the technical details of wind-wave coupling and multi-body coupling simulation, which fills the gap in the research of the wind-wave coupling and multi-body coupling numerical simulation of CWWHDs. Finally, the current research focus and development direction of CWWHDs and their numerical simulation technology are summarized to provide a reference for the future development and application of CWWHDs and numerical simulation technology.

Eugenol inhibits quorum sensing at sub-inhibitory concentrations - Liman Zhou; Hongda Zheng; Yidan Tang; Wengong Yu; Qianhong Gong (Biotechnology Letters, 2013)